High IgG titers against EBV glycoprotein 42 correlate with lower risk of nasopharyngeal carcinoma - Warner, Benjamin E.; Shair, Kathy H.Y. (The Journal of Clinical Investigation, 2025)
Serologic biomarkers for the early diagnosis of EBV-associated nasopharyngeal carcinoma (NPC) have been identified from population studies, but a protective antibody signature in cancer-free seropositive carriers remains undefined. In this issue of the JCI, Kong et al. show that high levels of IgG against EBV glycoprotein 42 (gp42) were associated with reduced NPC risk in three independent prospective cohorts from southern China. EBV virions contain gp42, which complexes with gH-gL to facilitate fusion with B cells by binding to HLA class II (HLA-II). In this study, HLA-II was detected on non-antigen-presenting cells in a proportion of premalignant nasopharyngeal tissues, which may prime the nasopharyngeal epithelium for infection. In vitro, HLA-II expression in a nasopharyngeal cell line encouraged infection by EBV derived from B cells or epithelial cells. These findings suggest that a vaccine that stimulates gp42-IgG production may reduce the risk of EBV-associated NPC in endemic regions.